Tryptophan Catabolism as Immune Mechanism of Primary Resistance to Anti-PD-1 - Botticelli, Andrea; Mezi, Silvia; Pomati, Giulia; Cerbelli, Bruna; Cerbelli, Edoardo; Roberto, Michela; Giusti, Raffaele; Cortellini, Alessio; Lionetto, Luana; Scagnoli, Simone; Zizzari, Ilaria Grazia; Nuti, Marianna; et al. (Frontiers in Immunology, 2020)
Backgrounds. Clinical trials showed that only a subset of patients benefits from immunotherapy suggesting the need to identify new predictive biomarker of resistance.. Indolamine 2,3-dioxygenase (IDO) has been proposed as a mechanism of resistance to anti-PD1 treatment and serum kyn/trp ratio represent a possible marker of IDO activity. Methods. Metastatic NSCLC, RCC and HNSCC treated in second line with nivolumab were included in this prospective study. Baseline serum kynurenine and tryptophan levels were measured by high-performance liquid chromatography to define the kyn/trp ratio. The 2–test and t-test were applied to compare frequencies and means values of kyn/trp ratio between subgroups with distinct clinic/pathological features, respectively. Median baseline kyn/trp ratio was defined and used as cut-off in order to stratify the patients. The association between kyn/trp ratio, clinic/pathological characteristics, response, progression-free survival (PFS) and overall survival (OS) was analyzed. Results. Fifty-five patients were included. Mean baseline serum kyn/trp ratio was significantly lower in female than male (0.048 vs 0.059, respectively, p=0.044) and in patients with lung metastasis than others (0.053 vs0.080, respectively, p=0.017). Mean baseline serum kyn/trp ratio was significantly higher in early progressors patients with both squamous and non-squamous NSCLC (p=0.003) and with a squamous histology cancer (19 squamous NSCLC and 14 HNSCC p=0.029). The median value of kyn/trp ratio was 0.06 in the overall population. Using median value as cut-off, patients with kyn/trp ratio >0.06 had a higher risk to develop an early progression (within 3 months) to nivolumab with a trend toward significance (p=0.064 at multivariate analysis). Patients presenting a baseline kyn/trp ratio ≤0.06 showed a longer PFS (median 8 versus 3 months; HR:0.49; 95% CI 0.24–1.02; p=0.058) and a significantly better OS compared to those with a kyn/trp ratio >0.06 (median 16 versus 4 months; HR:0.39; 95% CI 0.19–0.82; p=0.013). Conclusion. Serum kyn/trp ratio could have both a prognostic and predictive value in patients with solid tumor treated with immunotherapy, probably reflecting a primary immune-resistant mechanism regardless the primary tumour histology. Its relative weight is significantly related to gender, site of metastasis, NSCLC and squamous histology, although, these suggestive data need to be confirmed in larger studies.